Implementation Of Health Service Cost Accounting In Community Health Centers - Alya Rachmawati; Peza Bhakti Muzza; Dwi Noerjoedianto; Adila Solida (CV. AFDIFAL MAJU BERKAH, 2026)
Community Health Centers are first-level health service facilities that have a strategic role in providing healthcare services to the community. In the implementation of the National Health Insurance (JKN) program and the Financial Management Pattern of Regional Public Service Agencies (PPK-BLUD), Community Health Centers are required to implement efficient, transparent, and accountable financial management. One of the efforts that can be undertaken is the implementation of healthcare cost accounting to determine unit costs and to serve as a basis for determining rational service tariffs. This study aims to analyze the implementation of healthcare cost accounting in Community Health Centers based on the results of previous studies. The method used in this research is a systematic review with a PRISMA approach through the stages of identification, screening, eligibility, and inclusion of articles. Out of 150 identified articles, 7 articles met the inclusion criteria and were analyzed in this study. The results show that the Activity Based Costing (ABC) method is the most commonly used method and is considered more accurate than conventional methods in calculating the unit cost of healthcare services. The implementation of the ABC method is able to provide more detailed cost information, assist in evaluating service tariffs, and support cost control as well as the sustainability of healthcare services at Community Health Centers.